Formulasi Edible Film Antibakteri Ekstrak Daun Cengkeh (Syzygium aromaticum L.) Dengan Variasi Konsentrasi Sorbitol Sebagai Plasticizer - Ida, Nur; Rusli; Sriyanti (Jurusan Farmasi Poltekkes kemenkes Makassar, 2024)
Formulation of Antibacterial Edible film Clove Leaf Extract (Syzygium aromaticum l.) with variation sorbitol concentration as a plasticizer Edible film is a practical dosage form that can be developed as a carrier for anti-bacterial medicinal ingredients. The clove plant (Syzygium aromaticum L.) contains antibacterial compounds so it can be developed into an antiseptic edible film preparation. Differences in additional ingredients in edible film preparation can impact the physical attributes of the product. This research aims to assess the impact of sorbitol plasticizer concentration in the formulation of edible film preparation of Clove leaf extract (Syzigium aromaticum). The study also evaluates its antibacterial activity against porphyromonas gingivalis. The research methodology encompasses macerated extraction using 70% ethanol extract, minumum Inhibitory Concentration (MIC) testing, formulation of edible films with a 2,5%, concentration of clove leaf extract, and sequential variations in sorbitol concentration of as a plasticizer ( 0% - FI, 0,7% - F2, 1,4% - F3, 2,8% - F4), physical quality test include organoleptic tests, thickness tests, brittleness tests, and pH tests, followed by an antibacterial test of the prepared film. Results from the physical quality assesment for all formulas indicate that the organoleptic characteristis of edible film had a brown color, a characteristic odor, a soft texture, and a sweet taste, the thickness ranged form 0,10-0,11 mm, the friability ranged form 0,6-0,7% and the pH is 5,5. Antibacterial activity test results show inhibition zones ranging from 7,55±0,60-7,71±0,24 mm. The study’s conclusion reveals that variations in sorbitol plasticizer concentration of do not adversely affect the physical quality of edible film and it exhibits antibacterial activity against Porphyromonas gingivalis. Edible film adalah salah satu bentuk sediaan praktis yang berpeluang untuk dikembangkan sebagai pembawa bahan obat anti bakteri. Tanaman Cengkeh (Syzygium aromaticum L.) mengandung senyawa antibakteri sehingga berpeluang dikembangkan menjadi sediaan edible film antibakteri. Perbedaan bahan tambahan dalam sediaan edible film dapat berpengaruh terhapad mutu fisik sediaan termasuk bahan plasticizer. Riset ini dilakukan dengan tujuan untuk dan menentukan dampak perbedaan konsentrasi plasticizer sorbitol dalam formula edible film yang mengandung ekstrak daun cengkeh (Syzygium aromaticum L.) dan menentukan aktifitas antibakterinya terhadap Porphyromonas gingivalis.. Metode riset mencakup ekstraksi menggunakan maserasi cairan penyari etanol 70%, uji Konsentrasi Hambatan Minimum (KHM), formulasi edible film yang ditambahkan ekstrak daun cengkeh 2,5% dan variasi konsentrasi sorbitol sebagai plasticizer berturut-turut 0% (F1), 0,7% (F2), 1,4% (F3), 2,8% (F4), uji mutu fisik meliputi uji organoleptik, uji ketebalan, uji kerapuhan dan uji pH, dilanjutkan uji aktifitas antibakteri sediaan. Hasil pengujian mutu fisik pada semua formula menunjukkan data organoleptik edible film memiliki warna coklat, bau khas, tekstur lunak serta rasa manis, uji ketebalan berkisar 0,10-0,11 mm, uji kerapuhan berkisar 0,6-0,7% dan uji pH 5,5 dan hasil uji aktivitas antibakteri terhadap sediaan memiliki zona hambatan berkisar 7,55±0,60-7,71±0,24 mm. Kesimpulan penelitian menunjukkan bahwa variasi konsentrasi Plasticizer sorbitol tidak mempengaruhi mutu fisik edible film dan Edible film ekstrak daun cengkeh (Syzygium aromaticum L.) mampu menghambat pertumbuhan bakteri Porphyromonas gingivalis.